Free volumes in mixed-tacticity poly(3-hydroxybutyrate) determined by viscosimetry and their correlations with structural features and mechanical properties - Van Opdenbosch Daniel; Kretschmer Martin; Lieleg Oliver; Zollfrank Cordt (Applied Rheology, 2022)
The viscosities of poly(3-hydroxybutyrate) (PHB) with mixed tacticities were determined as functions of temperature and shearing rate via plate–plate viscosimetry, and fitted by a combined Herschel–Bulkley–Cross–Doolittle model while applying Carvalho et al.’s single-point correction. They were compared to values of slit viscosimetry, obtained during processing at a temperature of 428 K. In both cases, measured values and fitted model parameters as a function of tacticity exhibited a discontinuous behaviour at a fraction of meso diads of 0.7. To further investigate, we calculated values of vibrational and excess free volume. We found that these correlate with structural and external properties, some of which were reported in earlier works, namely the paracrystalline contents and specific volumes of the materials at room temperature, as well as their energies of fracture during tensile testing. These, in turn, correlate with the statistical averages of relative lengths of chain segments of similar a- or iso-tacticity. Hence, we found that expressing changing tacticities simply by a continuous progression of the fraction of meso diads is insufficient to trace associated discontinuities of the flow behaviour in mixed-tacticity PHB. We conclude that free volume is generated by polymer chain conformational disorder, which should be treated on the oligomeric chain segment level.